Analisis Pengaruh Pertumbuhan Ekonomi, TPT, Tingkat Kemiskinan, Prevalensi Stunting Terhadap Indeks Pembangunan Manusia di Jawa Timur - Rahman, Balqis Azhar Aulia; Wijaya, Riko Setya (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
A decrease in the Human Development Index (HDI) signifies the influence of various factors impacting human well-being within a region or country. Factors contributing to a decline in HDI encompass aspects related to education, health, and economic conditions. This study aims to analyze the impact of Economic Growth, TPT, Poverty Level, and the Prevalence of Stunting on HDI. Employing a quantitative analysis approach, the study investigates the relationships among these variables. Secondary data, sourced from BPS and other reliable outlets, are collected to identify the effects of Economic Growth, TPT, Poverty Level, and the Prevalence of Stunting on HDI. The research utilizes time series data spanning from 2013 to 2022. Multiple Linear Regression Analysis is employed to delve into the extent to which these variables contribute to changes in HDI. The results of the analysis, focusing on the period from 2013 to 2022, reveal that Economic Growth has no significant negative impact on HDI. Conversely, TPT exhibits a positive and significant association with HDI, whereas Poverty Level demonstrates a significant negative impact on HDI. However, the Prevalence of Stunting is found to have no significant effect on HDI during the specified period.